2001
DOI: 10.1099/00221287-147-5-1353
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the structure–function relationship of the S-layer protein SbsC of Bacillus stearothermophilus ATCC 12980 by producing truncated forms

Abstract: The mature surface layer (S-layer) protein SbsC of Bacillus stearothermophilus ATCC 12980 comprises amino acids 31-1099 and self-assembles into an oblique lattice type which functions as an adhesion site for a cell-associated highmolecular-mass exoamylase. To elucidate the structure-function relationship of distinct segments of SbsC, three N-and seven C-terminal truncations were produced in a heterologous expression system, isolated, purified and their properties compared with those of the recombinant mature S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(96 citation statements)
references
References 32 publications
(37 reference statements)
7
88
1
Order By: Relevance
“…This finding is in accordance with previous results that S-layer proteins formed sheet-like or fingerprint-shape structures in cytoplasm of the host cells. 24) No self-assembly product was observed in E. coli BL21 containing pET28a ( Fig. 4c and d), but negative staining study showed that the purified SlpC and ÁSlpC fusion protein had no sheet-like crystal lattice structure.…”
Section: Toxicity Of the Fusion Protein Of Slpcmentioning
confidence: 96%
“…This finding is in accordance with previous results that S-layer proteins formed sheet-like or fingerprint-shape structures in cytoplasm of the host cells. 24) No self-assembly product was observed in E. coli BL21 containing pET28a ( Fig. 4c and d), but negative staining study showed that the purified SlpC and ÁSlpC fusion protein had no sheet-like crystal lattice structure.…”
Section: Toxicity Of the Fusion Protein Of Slpcmentioning
confidence: 96%
“…All other investigated strains, such as G. stearothermophilus PV72/p6 (SbsA; Kuen et al, 1994;X71092) For the S-layer protein SbsC it was shown experimentally that a positively charged N-terminal fragment (amino acids 31-257) is responsible for anchoring the S-layer subunits. Using several truncated forms of SbsC it was demonstrated that this region is not required either for self-assembly or for generating the oblique lattice structure (Jarosch et al, 2001). Interestingly, none of the SCWPs of the organisms that possess S-layer proteins without SLH domains are modified with pyruvyl groups and some of them have a net-neutral charge (see Fig.…”
Section: Interactions Of Scwps and S-layers From Bacillaceaementioning
confidence: 99%
“…Electron microscopy and image analysis procedures have shown that all S-layer proteins possess two morphological domains (Baumeister et al, 1989;Engelhardt & Peters, 1998). Biochemical, biophysical and genetic approaches have shown that one of these domains is the cellwall-anchoring domain (Lupas et al, 1994;Mesnage et al, 1999;Jarosch et al, 2001;Smit et al, 2001;Rünzler et al, 2004). Gram-positive bacteria contain various anchoring domains that interact with different secondary cell wall polymers.…”
Section: Introductionmentioning
confidence: 99%
“…The other domain appears to be a crystallization domain (Bingle et al, 1987;Mesnage et al, 1997Mesnage et al, , 1999Howorka et al, 2000;Jarosch et al, 2001;Smit et al, 2002;Mader et al, 2004). Recent studies have focused on the structurefunction relationships of this domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation